2017
DOI: 10.1111/cge.12972
|View full text |Cite
|
Sign up to set email alerts
|

Dental and extra‐oral clinical features in 41 patients with WNT10A gene mutations: A multicentric genotype–phenotype study

Abstract: WNT10A gene encodes a canonical wingless pathway signaling molecule involved in cell fate specification as well as morphogenetic patterning of the developing ectoderm, nervous system, skeleton, and tooth. In patients, WNT10A mutations are responsible for ectodermal-derived pathologies including isolated hypo-oligodontia, tricho-odonto-onycho-dermal dysplasia and Schöpf-Schulz-Passarge syndrome (SSPS). Here we describe the dental, ectodermal, and extra-ectodermal phenotypic features of a cohort of 41 patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
3
23
1
Order By: Relevance
“…More recently, mutations in WNT10A (2q35; OMIM 606268) have been shown to be associated with EDI with both autosomal dominant and recessive inheritance . The WNT10A gene is implicated in the Wnt/beta‐catenin pathway, which together with the ectodysplasin signaling pathway plays a crucial role in tooth morphogenesis and the development of ectodermal structures …”
Section: Introductionmentioning
confidence: 99%
“…More recently, mutations in WNT10A (2q35; OMIM 606268) have been shown to be associated with EDI with both autosomal dominant and recessive inheritance . The WNT10A gene is implicated in the Wnt/beta‐catenin pathway, which together with the ectodysplasin signaling pathway plays a crucial role in tooth morphogenesis and the development of ectodermal structures …”
Section: Introductionmentioning
confidence: 99%
“…XLHED is due to mutations in the EDA gene (ectodysplasin-A), which maps to Xq12q13.1 and encodes ectodysplasin ( EDA ; OMIM 300451), a member of the tumor necrosis factor (TNF) family [Bayés et al, 1998]. Autosomal dominant (AD; OMIM 129490) and autosomal recessive (AR; OMIM 224900) forms of HED/EDA are encountered less frequently and result from mutations in the EDAR or in the EDARADD genes [van der Hout et al, 2008;Plaisancié et al, 2013]. Moreover, recently, it has been shown that mutations in the WNT10A gene are responsible for a broad spectrum of autosomal recessive ED [Cluzeau et al, 2011].…”
mentioning
confidence: 99%
“…In contrast, mutations in the WNT10A gene (OMIM 606268), encoding a protein that participates in the WNT/β-catenin/Lef-1 signaling pathway, have been shown to cause a highly variable phenotype, ranging from isolated tooth agenesis to ED syndromes such as odonto-onycho-dermal dysplasia (OODD; OMIM 257980) and Schöpf-Schulz-Passarge syndrome (SSPS; OMIM 224750) [Adaimy et al, 2007;Bohring et al, 2009;Cluzeau et al, 2011;Kantaputra et al, 2014]. The classic Wnt/β-catenin signaling pathway has been shown to play an essential role in odontogenesis, ectodermal development, and epidermal homeostasis [Tardieu et al, 2017].…”
mentioning
confidence: 99%
“…SSPS is speculated to be an autosomal recessive condition caused by mutations in the WNT10A gene, which plays roles in signaling molecule that regulates cell to cell interactions and in multiple developmental processes in embryogenesis including tooth morphogenesis . Hence, several studies have found WNT10A mutations to cause a range of phenotypes, with hypodontia being a consistent feature . However, as patients with odonto‐onycho‐dermal dysplasia and nonsyndromic hypodontia have also been reported to exhibit similar WNT10A mutations, these mutations cannot be considered to be pathognomonic of SSPS …”
Section: Introductionmentioning
confidence: 99%
“…Hence, several studies have found WNT10A mutations to cause a range of phenotypes, with hypodontia being a consistent feature . However, as patients with odonto‐onycho‐dermal dysplasia and nonsyndromic hypodontia have also been reported to exhibit similar WNT10A mutations, these mutations cannot be considered to be pathognomonic of SSPS …”
Section: Introductionmentioning
confidence: 99%